2021
DOI: 10.1186/s43055-021-00631-w
|View full text |Cite
|
Sign up to set email alerts
|

A multicentric observational study of imaging findings in COVID-19-related rhino-orbito-cerebral mucormycosis: a new Pandora’s box

Abstract: Background There is a sudden rise of fungal infection with corona virus disease. This is attributed to the immunomodulation by the disease and the drugs used, diabetes mellitus, steroid use, oxygen inhalation using dirty water, use of zinc and iron supplements, etc. Early diagnosis and prompt medical and surgical intervention is the mainstay of treatment. This can greatly reduce the high morbidity and mortality associated with this disease. The objective of the study is to describe the imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…4,8,9 Main MRI findings mentioned in literature in consistent with AIFS were LOCE and extrasinus invasion. 4,9,10 Many descriptive radiological studies in AIFS compare CT and MRI findings either in or before Covid-19 era. They concluded that contrast MRI study is better tool at demonstrating extrasinus, orbital, intracranial extensions in comparison to minimal CT findings.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…4,8,9 Main MRI findings mentioned in literature in consistent with AIFS were LOCE and extrasinus invasion. 4,9,10 Many descriptive radiological studies in AIFS compare CT and MRI findings either in or before Covid-19 era. They concluded that contrast MRI study is better tool at demonstrating extrasinus, orbital, intracranial extensions in comparison to minimal CT findings.…”
Section: Discussionmentioning
confidence: 89%
“…They concluded that contrast MRI study is better tool at demonstrating extrasinus, orbital, intracranial extensions in comparison to minimal CT findings. Moreover, both LOCE and extrasinus invasion had similar high specificity and sensitivity, LOCE showed wide observation range between two blinded observers 4,9 . Subsequently, many radiologists rely on extrasinus involvement rather than LOCE only.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations